Answer:
When there is not a constant rate of change
Step-by-step explanation:
A linear model shows a continuous response variable as a function of one or more predictor variables.
A linear model is a good fit for a set of data when the plotted points show a constant rate of change.
When a plot of values form a scatter plot, it is difficult to identify a linear model because the points will not appear to follow a trend.
To come up with a linear function in this case will require you to identify the line of best fit then extending the line to y-axis intercept so as to be able to find the slope.
If a number is not a natural number then it is not a whole number
Answer:
no
Step-by-step explanation:
a natural number has to be a whole number
Solve for x: 7(x - 2) = 5(x + 4)
7(x - 2) = 5(x + 4)
Multiply the first bracket by 7
(7)(x)=7x
(7)(-2)=-14
Multiply the second bracket by 5
(5)(x)=5x
(5)(4)=20
7x-14=5x+20
Move 5x to the other side. Sign changes from -5x to +5x.
7x-5x-14=5x-5x+20
7x-5x-14=20
2x-14=20
2x-14+14=20+14
2x=34
Divide both sides by 2
2x/2=34/2
Answer: x=17
Answer:
7(x-2)=5(x+4)
7x-14=5x+20
7x-5x=20+14
2x=34
x=17
Tasha eats half her snack and gives the other half to her two best friends for them to share equally. What portion of the whole snack does each friend get? Draw a picture to support your response.
Each of Tasha's friends receives one-quarter (¼) of the whole snack after she eats half and divides the remainder equally between them.
Explanation:To determine what portion of the whole snack each of Tasha's two best friends gets, let's first understand the portions.
Tasha eats half of the snack, leaving the other half to be shared equally between her two friends.
Since there are two friends, the remaining half is divided into two equal parts.
Mathematically, when the remaining half (½) of the snack is divided equally among two people, this half is further divided by 2, which is the same as multiplying by ½ (since dividing by a number is the same as multiplying by its reciprocal).
So, the calculation would be ½ (remaining portion) × ½ (each friend's share) = ¼.
Therefore, each of Tasha's friends gets one-quarter (¼) of the whole snack.
We can visualize this through a drawing not included here, but imagine a circle (representing the snack) divided into 4 equal parts. Tasha eats 2 parts (half), and each friend gets 1 part (one-quarter).
The portion of the whole snack each friend gets is 1/4
What portion of the whole snack does each friend get?
From the question, we have the following parameters that can be used in our computation:
Proportion eaten = 1/2
Proportion to friends = 1/2
There are 2 friends
So, the portion of the whole snack each friend gets is
Each friend = 1/2 ÷ 2
Rewrite as
Each friend = 1/2 * 1/2
Evaluate
Each friend = 1/4
Hence, the portion of the whole snack each friend gets is 1/4
division of whole numbers
Answer:
The number 24 is called the dividend ('that which is to be divided'). The number 8 is called the divisor ('that which divides'). The number 3 is called the quotient, (from the Latin quotiens meaning 'how many times'). Division without remainder can be visualized as skip-counting.
When a number, n, is increased by two and then the result is divided by
Write an equation and solve it to find the value of n.
ult is divided by five the quotient is equal to 14.
Answer:
n=68
Step by step explanation:
When a number n is increased by two means n+2 so we can put parenthesis around it
(n+2)/5 = 14
now we solve for the equation (for the variable n)
First multiply both sides by 5 to isolate the parenthesis on the left side by itself
(n+2) = 14*5
then we can simply isolate n by itself by subtracting both sides by 2
n = 70 -2 = 68
n = 68
To find the value of n when [tex]\frac{(n + 2) }{5}[/tex] = 14, resulting in n = 68.
The question asks to define an equation based on a described operation with a given result, and then solve it to find the value of n. The operation described is increasing a number n by two, then dividing the result by five to get a quotient of 14.
To translate this into an equation, you would set up the following equation:
[tex]\frac{(n + 2) }{5}[/tex] = 14
To find the value of n, you would first multiply both sides by 5 to isolate n on one side:
n + 2 = 70
Then, subtract 2 from both sides to solve for n:
n = 68
Therefore, the value of n is 68. This solves the equation and provides the value that n must be for the operation to result in a quotient of 14.
A group of friends about two large pizzas at 8 only part each Pizza how many pieces that they eat
Answer:
16 pizza's
Step-by-step explanation:
you multiple 8 x 2 which is 16
1. The sum of two integers cannot be 0, True or False?
2. The sum of two negative integers is always a negative integer, True or False?
3. What number must you add to -6 to get a sum of zero
[tex]\huge\boxed{\text{1. False}}[/tex]
Integers are the numbers in the set [tex]{..., -3, -2, -1, 0, 1, 2, 3, ...}[/tex]. This means that you can add two opposite integers to get [tex]0[/tex].
For example, [tex]-3+3=0[/tex].
[tex]\huge\boxed{\text{2. True}}[/tex]
When you add a negative number to another negative number, the only thing that can happen is that the result goes down.
For example, [tex](-3)+(-2)\ =\ -3-2\ =\ -5[/tex].
[tex]\huge\boxed{\text{3. 6}}[/tex]
Let's write this as an equation, where [tex]x[/tex] represents the unknown value. [tex]-6+x=0[/tex]
We need to isolate the variable by adding [tex]6[/tex] on both sides of the equation. [tex]x=\boxed{6}[/tex]
Answer:
1) false example -1+1=0
2) true
3) 6
Determine if x - 2 is a factor of p(x) = x4 - 3x2 + 2x - 8, and explain why.
Answer:
If x-2 is a factor of p(x) = x^{4} - 3 x^{2} + 2 x - 8 ,then p(x) = 0
Solution:
According to factor theorem of polynomials,
x-a is a factor of polynomial p(x), if and only p(a)=0
Step 1:
Since x-2 is factor of p(x),
x - 2 = 0
x = 2
Step 2:
[tex]p(x) = x^{4} - 3 x^{2} + 2 x - 8 ------ (equation 1)[/tex]
By substituting x = 2 in equation 1,
[tex]p(x) = 2^{4} - 3(2)^{2} + 2(2) - 8[/tex]
p(x) = 16 - 3(4 ) + 4 -8
p(x) = 16 - 12 - 4
p(x) = 16 - 16
p(x) = 0
Since x - 2 is a factor of p(x) , we get p(x)=0
please solve -2(x - 4)= -8
Answer:
x = 8
Step-by-step explanation:
First distribute the -2 to (x - 4), -2 × x is -2x and -2 × -4 is 8. The equation should now look like this, -2x + 8 = -8. Then subtract the positive 8 from both sides, giving you, -2x = -16. Then divide both sides by -2 and you should get 8 as your answer.
Answer: x=8
Step-by-step explanation:
-2(x-4)=-8
divide both sides
x-4=4
move constant to the right
x=4+4
add the number
x=8
I hope it helped!
(3 x 10) X 8 =_
X (10 X 8)
Uruekne kdnbfbd
Step-by-step explanation:
(3 × 10) × 8 = 3 × (10 × 8)
It's an Associative Property of addition:
(a + b) + c = a + (b + c)
Check it:
Left side: (3 × 10) × 8 = 30 × 8 = 240
Right side: 3 × (10 × 8) = 3 × 80 = 240
CORRECT
......is an example of
Answer:
The answer would be 'D'.
Step-by-step explanation:
An expression does NOT have an equal sign while a formula does. A variable is some letter symbol that you are solving for, but a constant would be a number such as 2 or 4 that could be added, multiplied, subtracted, or divided in an equation.
I hope this helps!
Answer:
Step-by-step explanation:
a formula
(15-3)÷12+1
How to divide this without using a remainder?
Answer:
If you solved this, it wouldn't have a remainder. First you would solve the numbers in the parenthesis, (15 - 3), which is 12. Now it should look like, 12 ÷ 12 + 1. Next you divide 12 by 12 and that equals 1. And all you need to do now is add 1 + 1, which is 2. So your answer will be 2.
Answer:
2
Step-by-step explanation:
To be able to solve this equation, you would use PEMDAS. This stands for the order of operations, and which order you would do them in. P stands for parenthesis, E stands for exponents, M stands for multiplication, D stands for division, A stands for addition, and S stands for subtraction. Using this order, you would solve what is inside the parentheses first. So, 15-3 is 12. Once this piece is solved, you would have 12÷12+1. Then, since you don't have any exponents or multiplication, you would skip to division. 12 ÷ 12 is 1. So then your equation would be: 1+1. 1+1 is equal to 2. So your answer is 2! There is not remainder in the solution of this problem.
Camille is taking a quiz on a computer.The computer says her score is 0.625. Which fractions are equivalent to 0.625?
Answer:
5/8
Step-by-step explanation:
0.625
625/1000
125/200
25/40
5/8
Answer:
there are many possible answers, but some samples are 625/1000, 125/200, 25/40, and 5/8.
Step-by-step explanation:
I just turned the decimal into a fraction using a simple method where, say, if the decimal went to the thousandths place value, like this one does, we put the decimal over 1000. If the number goes to the hundredths place, we put it over 100, etc. Then I simplified it a few times (by dividing both the numerator and denominator by 5) to get some more equivalent fractions (although you could multiply upwards and get fractions like 3125/5000 which would still be equivalent because I multiplied both the numerator and denominator, though that's besides the point) and ended up with the fully simplified fraction of 5/8.
Hope this helps! :3
Abe has a coupon for bread: Buy one loaf, get the second free. A loaf of bread costs $2.50. If Abe buys two loaves of bread, what is the price
after using the coupon?
$1.25
$3.75
$5.00
$2.50
The total cost Abe needs to pay is the cost of one loaf, which is $2.50. Hence, the correct answer is $2.50.
Answer Explanation:Let's solve this question step by step:
Step 1: We know Abe has a coupon that allows him to buy one loaf and get the second free.
Step 2: The cost of a single loaf of bread is given as $2.50.
Step 3: As per the coupon, if Abe buys two loaves of bread, he is only required to pay for one. This means he needs to pay for one loaf only.
Step 4: Therefore, the total cost Abe needs to pay is the cost of one loaf, which is $2.50.
Hence, the correct answer is $2.50.
#SPJ2
One Solution
no solution
infinitely many solutions
3x + 9 + 4x + x =
_x+_
The simplified equation from the given 3x + 9 + 4x + x = _x + _ is 8x + 9 = _x + _. This equation cannot be solved further without the values for the variables represented by the underscores.
Explanation:The first step to solving the equation is to simplify it. Your original equation is 3x + 9 + 4x + x = _x + _. When we simplify the left side of the equation by combining like terms we get 8x + 9 = _x + _. However, the variables in the blanks on the right side of equation are unknown, so we can't solve it fully. But now you have a simpler equation to work with, and if you receive any additional information, you can substitute those values into your simplified equation.
Learn more about Solving Algebraic Equations here:https://brainly.com/question/33839116
#SPJ12
Determine if the equation
y = 2/5 x − 4
represents a proportional relationship. If so, determine the constant of proportionality.
Answer:
The given equation not represent a proportional relationship
Step-by-step explanation:
we know that
A relationship between two variables, x, and y, represent a proportional variation if it can be expressed in the form [tex]y/x=k[/tex] or [tex]y=kx[/tex]
In a proportional relationship the constant of proportionality k is equal to the slope m of the line and the line passes through the origin
In this problem we have
[tex]y=\frac{2}{5}x-4[/tex]
This line not passes through the origin
Verify
For x=0
[tex]y=\frac{2}{5}(0)-4=-4[/tex]
therefore
The given equation not represent a proportional relationship
Find the product using suitable identities.
a) [tex](\frac{x}{3} - 6)^{2}[/tex] step by step
Answer:
[tex]\frac{x^2}{9}[/tex] - 4x + 36
Step-by-step explanation:
([tex]\frac{x}{3}[/tex] - 6)² = ([tex]\frac{x}{3}[/tex] - 6)([tex]\frac{x}{3}[/tex] - 6)
Each term in the second factor is multiplied by each term in the firs t factor, that is
[tex]\frac{x}{3}[/tex]([tex]\frac{x}{3}[/tex] - 6) - 6([tex]\frac{x}{3}[/tex] - 6)
Distribute both parenthesis
= [tex]\frac{x^2}{9}[/tex] - 2x - 2x + 36 ← collect like terms
= [tex]\frac{x^2}{9}[/tex] - 4x + 36
Express twenty-nine thousandths as a fraction
Answer:
29/1000
Step-by-step explanation:
Answer:
29/1,000
Step-by-step explanation: it says thousands so u put thousand at the bottom then you put 29 on top
Three cars are for sale,
Car A
£12380
Car B
£16760
Car C
£14580
The price of each car is rounded to the nearest £100.
Which price changes by the greatest amount?
You must show your working,
Final answer:
Upon examining the prices of the three cars and calculating the potential original price before rounding, we find that all three cars could have a maximum price change of £49 when rounded to the nearest £100. Therefore, all cars have the same greatest potential change in price.
Explanation:
To determine which car's price changes by the greatest amount when rounded to the nearest £100, we need to consider the possible original prices before rounding. The original price could be up to £49 above or £50 below the rounded price, as values are rounded up when they reach the halfway point (£50).
Car A
Price: £12,380. Possible price range before rounding: £12,350 to £12,429.
Car B
Price: £16,760. Possible price range before rounding: £16,750 to £16,809.
Car C
Price: £14,580. Possible price range before rounding: £14,550 to £14,629.
Now, we must calculate the maximum changes in price. The greatest amount of change occurs when the original price is at the extreme end of the range.
With each car having a possible maximum change of £49, it means that all cars could potentially have the same greatest amount of change.
What would 672,831 be rounded to the nearest hundred
Answer:
672,800
Step-by-step explanation:
672,800 672800
HEEEELP PLEASE
I dont understand
Answer:
y = 0.5xStep-by-step explanation:
[tex]\dfrac{y}{x}=a\to y=ax\\\\\text{We have}\ x=1,\ y=0.5.\\\\\text{Substitute:}\\\\a=\dfrac{0.5}{1}=0.5\\\\\text{Therefore}\ y=0.5x[/tex]
Answer:
y = 0.5x
Step-by-step explanation:
x = 1; y = 0.5; 0,5 is [tex]\frac{1}{2}[/tex] of 1
1 * 0.5 would equal 0.5
So, y = 0.5x
Hope this helps :)
Write a number in each box to make an equation that has no real solution. Explain why this equation has no solution. 4(a-2) + a = __a - __
Answer:
4(a-2)+a=4a-2 No solution
Step-by-step explanation:
This would never be true. Try plugging in a as 1.
4(1-2)+1 isn't equal to 4(1)-2.
What is the image point of (5,2) after a translation left 1 unit and down 2 units?
Answer:
(4, 0 )
Step-by-step explanation:
A translation of 1 unit left, subtract 1 from the original x- coordinate
A translation of 2 units down, subtract 2 from the original y- coordinate
The rule is (x, y ) → (x - 1, y - 2 ), thus
(5, 2 ) → (5 - 1, 2 - 2 ) → (4, 0 )
The image point of (5,2) after a translation left 1 unit and down 2 units is (4, 0).
Explanation:To find the image point of (5,2) after a translation left 1 unit and down 2 units, we need to subtract 1 from the x-coordinate and subtract 2 from the y-coordinate.
The translated image point would be (5-1, 2-2) = (4, 0).
So, the image point of (5,2) after the translation left 1 unit and down 2 units is (4, 0).
Learn more about Translation here:https://brainly.com/question/38241586
#SPJ2
What is an equation of a line perpendicular to 5x+8y=16 and passed through (-5,7)
Answer:
y = (8/5)x + 15
Step-by-step explanation:
First change the equation to standard form (y=mx+b)
5x + 8y = 16
8y = 16 - 5x
y = - (5/8)x + (16/8)
y = - (5/8)x + 2
Perpendicular Lines have the inverse opposite sign of slope
[For example: inverse opposite sign of 2 is - (1/2)]
Original equation slope (m) : - (5/8)
2nd Equation (m) : 8/5
After finding the slope, plug in the slope and points the standard form equation (y=mx+b)
Point: (-5,7) x : -5 y : 7
Slope (m) : 8/5
y = m x + b
7 = (8/5) (-5) + b
'b' is the y-intercept and the last thing to solve for the equation
7 = - 8 + b
15 = b
Now, put the slope (m) and y-intercept (b) back into the equation
y = (8/5)x + 15
Halle el valor de x de tal forma que la distancia entre los puntos dados sea de 2V5 unidades.
b) (2x – 1,2) y (1 + x,x + 4)
Answer:
The value of x is [tex](+/-)\sqrt{6}[/tex]
Step-by-step explanation:
The question in English is
Find the value of x so that the distance between the given points is 2V5 units.
(2x - 1,2) and (1 + x,x + 4)
we know that
the formula to calculate the distance between two points is equal to
[tex]d=\sqrt{(y2-y1)^{2}+(x2-x1)^{2}}[/tex]
substitute the values
[tex]d=\sqrt{(x+4-2)^{2}+(1+x-2x+1)^{2}}[/tex]
[tex]d=\sqrt{(x+2)^{2}+(-x+2)^{2}}[/tex]
[tex]d=\sqrt{x^2+4x+4+x^2-4x+4}[/tex]
[tex]d=\sqrt{2x^2+8}[/tex]
Remember that
[tex]d=2\sqrt{5}\ units[/tex]
substitute
[tex]2\sqrt{5}=\sqrt{2x^2+8}[/tex]
squared both sides
[tex]20=2x^2+8\\\\2x^{2}=12\\\\x^{2}=6\\\\x=(+/-)\sqrt{6}[/tex]
therefore
The value of x is [tex](+/-)\sqrt{6}[/tex]
** A rock is thrown upward from the top of
a 25 foot tower with an initial upward
velocity of 100ft/sec. The height of a rock
above the ground as a function of time can
be modeled by the equation: h(t) =
- 16t? + 100t + 25. How long does it take
for the rock to fall back to the ground?
Answer:
The rocket will take 6.49 seconds to fall back to the ground
Step-by-step explanation:
* Lets explain how to solve the problem
- A rock is thrown upward from the top of a 25 foot tower with an initial
upward velocity of 100 ft/sec
- That means at t = 0 the height of the rock is 25 feet above the ground
- A function of time can be modeled by the equation:
h(t) = - 16t² + 100t + 25, where h is the height of the rocket from the
ground at time t
∵ h(t) = -16t² + 100t + 25
- The height of the rocket is 25 feet above the ground when it
is thrown up
∴ h(t) = 25 at t = 0 ⇒ initial position of the rocket
- The height of the rocket when hits the ground is zero
∴ h(t) = 0 when the rocket hits the ground ⇒ final position of it
- We need to find the time that the rocket takes to fall back to
the ground
∵ h(t) = 0
∵ h(t) = -16t² + 100t + 25
∴ -16t² + 100t + 25 = 0
- Lets solve it to find the value of t
∵ -16t² + 100t + 25 = 0
- Multiply both sides by -1 to make the coefficient of t² positive
∴ 16t² - 100t - 25 = 0
- Use your calculator to find the values of t
∴ t = 6.49 sec and t = -0.24 sec
∵ We will reject the value of t = -0.24, because time can not be
negative value
∴ The rocket will take 6.49 seconds to fall back to the ground
Two numbers total 68 and have a difference of 8
Answer: The smaller number is 30, the larger is 38
Step-by-step explanation:
x + (x - 8) = 68
2x - 8 = 68
2x = 60
x = 30
Starting from the origin, how is point ( – 5, 4) plotted?
Question 1 options:
Move 5 units left and 4 units up.
Move 5 units down and 4 units right.
Move 4 units down and 5 units right.
Move 4 units left and 5 units up.
Move 5 units left and 4 units up
Final answer:
To plot the point (-5, 4) from the origin, move 5 units to the left and 4 units up in a standard Cartesian coordinate system.
Explanation:
To plot the point (-5, 4) starting from the origin in a standard Cartesian coordinate system, you would need to move 5 units left and 4 units up. This is because the x-coordinate is negative, indicating a movement to the left of the origin, and the y-coordinate is positive, indicating a movement above the origin.
The correct steps are as follows:
Starting at the origin (0,0), move 5 units to the left along the horizontal axis. This brings you to the point (-5,0).From there, move 4 units upward along the vertical axis. This brings you to the final position, which is the point (-5, 4).This method adheres to the standard convention that in an xy-coordinate system, right and up are positive directions, while left and down are negative.
The score increased by 8 points.
Answer: S+8
Step-by-step explanation:
The score increased by 8
Let S represent the score
Increased means additional
Hence the equation is
S+8
Algebraic expression:
S = Score
S+8
Increased means add 8. Then, add 8 to the score which is "S" S would be the more common variable in which you will use here.
What is 5812 as a mixed number in simplest form?
Enter your answer in the box.
Answer:
[tex]5811 \frac{1}{1} [/tex]
Step-by-step explanation:
You could do this.
I am joyous to assist you anytime.